1990
DOI: 10.1128/mcb.10.8.4100
|View full text |Cite
|
Sign up to set email alerts
|

A transcription factor interacting with the class I gene enhancer is inactive in tumorigenic cell lines which suppress major histocompatibility complex class I genes.

Abstract: AKR leukemias display different amounts of major histocompatibility complex class I antigens on the cell surface. The absence of H-2Kk molecules correlates with the ability of these cell lines to form tumors in vivo as well as to escape lysis by cytotoxic T lymphocytes in vitro. In this report it is shown that the 5' regulatory area of the H-2Kk gene failed to activate transcription in H-2Kk-negative cells. Examination of the proteins interacting with the H-2Kk enhancer in expressing and nonexpressing cells re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
1

Year Published

1991
1991
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 59 publications
1
9
1
Order By: Relevance
“…P2m expression, (ii) defects in assembly or peptide loading (24), and (iii) regulatory defects as described by Henseling et al (25), Lenardo et al (26), and this paper.…”
supporting
confidence: 66%
“…P2m expression, (ii) defects in assembly or peptide loading (24), and (iii) regulatory defects as described by Henseling et al (25), Lenardo et al (26), and this paper.…”
supporting
confidence: 66%
“…Therefore, while classical class I antigen expression is often reduced or even absent (K k-and D k-expression in some AKR leukemias ( Fig. 3; Henseling et al 1990), and in primary AKR thymomas (data not shown) Q5 k expression seems to be augmented in the transformed tissue respectively cell lines. Thus, the Q5 k gene product might represent the novel H-2 class I "allo" specificity, characterized by Labeta and co-workers (1989) on Q5 ~ expressing tumor cell lines.…”
Section: Comentioning
confidence: 86%
“…Altered binding of regulatory factors to the MHC class I HC gene enhancer element by methylation or changes in the chromatin structure results in MHC class I HC mRNA down-regulation and consequently in a reduced expression of these molecules on the cell surface ( Fig. 5.9) [52,53].…”
Section: Mhc Class I Down-regulationmentioning
confidence: 99%